2023
DOI: 10.1161/circresaha.122.322264
|View full text |Cite
|
Sign up to set email alerts
|

PDE10A Inactivation Prevents Doxorubicin-Induced Cardiotoxicity and Tumor Growth

Abstract: BACKGROUND: Cyclic nucleotides play critical roles in cardiovascular biology and disease. PDE10A (phosphodiesterase 10A) is able to hydrolyze both cAMP and cGMP. PDE10A expression is induced in various human tumor cell lines, and PDE10A inhibition suppresses tumor cell growth. Chemotherapy drug such as doxorubicin (DOX) is widely used in chemotherapy. However, cardiotoxicity of DOX remains to be a serious clinical complication. In the current study, we aim to determine the role of PDE10A and the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Since renal inflammation can arise from CP-induced oxidative stress and apoptosis, PDE emergence as a nephrotoxic mediator further rationalizes PV's protective effects, given precedents of PDE inhibition managing inflammatory diseases including COPD, IBD, psoriasis, and CNS inflammation [38,39]. It has been reported that inhibitors of PDE10 have potential therapeutic effects in several diseases, including neurological diseases [14] and cardiotoxicity [40].…”
Section: Discussionmentioning
confidence: 99%
“…Since renal inflammation can arise from CP-induced oxidative stress and apoptosis, PDE emergence as a nephrotoxic mediator further rationalizes PV's protective effects, given precedents of PDE inhibition managing inflammatory diseases including COPD, IBD, psoriasis, and CNS inflammation [38,39]. It has been reported that inhibitors of PDE10 have potential therapeutic effects in several diseases, including neurological diseases [14] and cardiotoxicity [40].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, DIC can be alleviated by activating some classical signaling pathways such as cAMP/PKA/SIRT1 (Hu et al, 2020), or AKT/SIRT3/SOD2 (Liu et al, 2022). Recently, some potential DIC therapeutic targets have been newly discovered, such as PDE10A (Chen et al, 2023), Sestrin 2 (Wang et al, 2022a), FAM134B (Qu et al, 2022), TFEB (Chen et al, 2022), etc., which play a cardioprotective role in reducing apoptosis, improving cardiac function, reducing oxidative stress and endoplasmic reticulum stress, and promoting autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…PDE10A deficiency or inhibition reduces the apoptosis, malfunction, and atrophy caused by DOX. Recent findings suggest that inhibiting PDE10A attenuates DOX-induced cardiotoxicity and prevents cancer growth, and thus could be a promising strategy in cancer therapy [157,158].…”
Section: Gsh Depletion and Topo-drug Resistancementioning
confidence: 99%